PENDIDIKAN ANAK DALAM PANDANGAN HADIS NABI: RELEVANSINYA TERHADAP KONSEP HUKUM KELUARGA ISLAM : the Concept of Islamic Family Law - Muchtar, Zulayka; Amin , Muhammadiyah; Hafid , Erwin; Marwing, Anita (Muadalah : Jurnal Hukum, 2025)
This study aims to examine the hadiths of the Prophet Muhammad (peace be upon him) relating to child education within the family and to examine their relevance to the concept of Islamic family law. Through a thematic approach to authentic hadiths, this study outlines parents' responsibilities in instilling religious values, morals, and character formation in children from an early age. The results of the study indicate that child education is an integral part of parental obligations recognized in Islamic family law, not only as a moral responsibility but also as a legal obligation. The Prophet's hadiths provide a strong foundation for establishing an educational system within Muslim families, while emphasizing the importance of parents' active and consistent role in fostering their children's spiritual and social development. This study recommends strengthening parents' religious understanding as a basis for fulfilling their obligation to educate children within the context of Islamic family law.